Do schools in Quebec foster healthy eating? An overview of associations between school food environment and socio-economic characteristics. Issue 9 (16th January 2015) - Morin, Pascale; Demers, Karine; Robitaille, Éric; Lebel, Alexandre; Bisset, Sherri
Abstract: Objective: A school environment that encourages students to opt for food with sound nutritional value is both essential and formative in ensuring that young people adopt healthy eating habits. The present study explored the associations between the socio-economic characteristics of the school environment and the school food environment. Design: A cross-sectional survey was conducted in 2008–2009. Descriptive and bivariate analyses were performed on data from public primary and secondary schools. Setting: Quebec, Canada. The school food offering was observed directly and systematically by trained research assistants. Interviews were conducted to fully describe food offerings in the schools and schools' child-care services. Subjects: A two-stage stratified sampling was used to build a representative sample of 143 French-speaking public schools. The response rate was 66·2 %. Results: The primary and secondary schools in low-density areas were more likely to be located near diners (primary: P =0·018; secondary: P =0·007). The secondary schools in deprived areas were less likely to have a regular food committee ( P =0·004), to seek student input on menu choices ( P =0·001) or to have a long lunch period ( P =0·010). The primary schools in deprived areas were less likely to have a food service ( P =0·025) and their meal periods were shorter ( P =0·033). Conclusions: The schools in areas with lower socio-economic status provided an environment less favourable for a healthy diet. From a public health perspective, the results of this analysis could assist policy makers and managers to identify actions to support the creation of favourable school environments.